Analysis of The Implementation of Transit Oriented Development (TOD) Policies to Optimize the Integration of Public Transportation Modes - Oktafianus, Cokky; Fachrial, Peppy; Kania, Dinar Dewi (Dinasti International Journal of Digital Business Management, 2024)
Efforts to reduce congestion in Jakarta are by providing Transit-Oriented Areas (KBT) connected to several other modes of public transportation, such as Kereta Cepat Indonesia (KCI), LRT, MRT, and Transjakarta. The central government's plan related to Transit-Oriented Areas, the DKI Provincial Government has issued Perda 1/2012 concerning the 2030 regional spatial plan in Chapter 1 Article 75 "Transit-oriented development or Transit Oriented Development, hereinafter abbreviated as TOD, is an integrated area of various functional city activities with local and inter-local connectors". Transit-oriented development (TOD) standards aim to ensure the right of all people to access the city by walking and cycling safely to their destinations by fast and regularly scheduled public transport quickly and affordably and to live a healthy life without relying on private vehicles. This type of research is quantitative, using stakeholder and purposive sampling techniques. The results showed that overall, although the Dukuh Atas area has fulfilled several urban planning principles well, several areas still need to be improved, especially related to bicycle infrastructure, pedestrian accessibility, residential density, and affordable housing prices.